(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Experimental investigation of high performance and low emission colorless combustion in a micro gas turbine tubular combustor with multi-line of fuel injection located in secondary zone carried out at the atmospheric conditions, colorless oxidation reaction is characterized by dispersed homogenies flame and high uniformity of average temperature inside the combustion chamber. System performance, emission gases, the flame capturing photo, measurements of temperature, inlet air mass flow rate and gas fuel LPG flow rate for variable of fuel lines mass fraction F2/F1 are recorded at low emission colorless combustion condition. for 3.2 g/s of fuel flow rate with 6 holes and 1mm main injector holes diameter and 8 holes with 0.8mm diameter for secondary line of fuel injection, concluded that maximal air mass flow rate, with choked fuel flow in the main injector for each cases promotes the formation of colorless distributed pal blue flame combustion, with great effects for the equivalence ratio on the average temperature to limiting cooled flame quenching generation, desirable pattern factor < 0.28, increasing in combustion efficiency up to 99.68%, and decreasing in specific fuel consumption with rising of power generation.